EFFECTS OF BANANA STALK BIOCHAR ON THE PHYSICAL AND CHEMICAL PROPERTIES OF SOILS - Tayo, Badmus; Eludire, Oluwadamilare Oluwasegun; Udoh, Glory Nyong; Aderounmu, Ridwan; Olaoye, Saheed A; Ajayi, Ayodele Ebenezer; Faloye, Oluwaseun Temitope; Famuwagun, Idowu Bamidele; Ubi, Paschal Ateb (FUDMA JOURNAL OF SCIENCES, 2025)
Banana stalk biochar is a low-cost soil amendment with potential to improve degraded soils, yet its effects across contrasting textures remain under-reported. This study evaluated the effects of banana stalk biochar on the physical (bulk density, total porosity, water-retention capacity) and chemical properties (pH, organic carbon, exchangeable bases, available P, exchangeable acidity, CEC) of sandy loam (SL) and sandy clay (SC) soils. A randomized design with three biochar rates (0%, 3%, 6% w/w) and three replicates per soil was run for four weeks; soils received 500 mL water every 48 h, and data were analysed by two-way ANOVA with Tukey’s test (α = 0.05). Biochar significantly reduced bulk density (Soil: p < 0.001; Biochar: p = 0.002; interaction ns), from 1.82 g cm⁻³ (SC-0%) to 1.48 g cm⁻³ (SL-6%). Total porosity increased markedly (all main effects and interaction p < 0.001; R² = 99.88%), peaking at 0.322 cm³ cm⁻³ (SL-6%) versus 0.154 cm³ cm⁻³ (SC-0%). Water-retention capacity also rose with biochar (Soil and Biochar p < 0.001; interaction ns), from 93.67 mL (SL-0%) to 127.00 mL (SC-6%) with a strong model fit (R² = 95.93%). Chemically, biochar increased pH, organic carbon, available P, exchangeable K, Ca, and Mg, reduced exchangeable acidity, and raised CEC, with improvements more pronounced at 6% and generally stronger in SC than SL. Banana stalk biochar consistently enhanced soil structure and fertility across textures, indicating a practical pathway to improve water storage, nutrient retention, and physical quality in resource-constrained systems.